The errors of EFL students’ TOEFL iBT integrated writing task - Nurhayati Irmawan; Rahmi Aulia Nurdini (Journal of Research on English and Language Learning (J-REaLL), 2020)
Reading, Listening, Speaking and Writing are four skills tested in TOEFL iBT. The two types of questions in the writing task of TOEFL iBT are independent and integrated. Focusing on the integrated task in which test-takers require to read a passage, to listen to a lecture related to the topic of the reading and to summarize the listening by explaining how it relates to the points in the reading (Peterson, 2007:8). This research analyzed the errors of students' writing production of integrated task. The research samples of the task were taken from 7 (seven)  TOEFL iBT candidates. Examining 14 integrated tasks, this study categorized the errors into three major categories: grammar, mechanics, and content errors. This study found that most frequent grammatical errors were in the verb (22%),  agreement (20%), and followed by a noun (14%). The findings of mechanic errors are mostly in the use of capitalization at the beginning of a sentence. In the part of punctuation errors, it was found that the omission of a comma as a frequent error. The last results are content errors which consist of plagiarism;  own idea addition; question addressing in which if the test takers’ response focuses on one of the two passages and completely ignores the other one; and missed information in which test-takers are unable to absorb key information from reading and listening passage. It is expected that these findings enable TOEFL iBT tutors to recognize candidates' problems and improve their teaching approach to reach better results. Keywords: Error Analysis, TOEFL iBT, integrated writing task, summarizing